Daytime fatigue as a predictor for subsequent retirement among older New Zealand workers - Myllyntausta Saana; Gibson Rosemary; Salo Paula; Allen Joanne; Gander Philippa; Alpass Fiona; Stephens Christine (ELSEVIER, 2022)
Objectives: There is limited information on the role of fatigue on retirement, either independently or in association with poor sleep. The aim of this study was to examine the prospective association between daytime fatigue, measured as feeling tired or feeling worn out, independently and in relation to dissatisfaction with sleep, and subsequent retirement among 960 older workers in New Zealand.
Methods: Data from 2 consecutive surveys (2008 and 2010) of the New Zealand Health, Work, and Retirement Longitudinal Study were used. Poisson regression was used to investigate whether feeling tired and feeling worn out in 2008, along with dissatisfaction with sleep, were associated with self-reported retirement either due to health reasons or other reasons by 2010.
Results: The risk for retirement due to health reasons during a 2-year follow-up was 1.80-fold (95% confidence interval [CI] 1.16-2.45) among those who felt tired and 1.99-fold (95% CI 1.34-2.64) among those who felt worn out when compared to those not tired or not feeling worn out after adjusting for several sociodemographic, work characteristics and self-rated health. The risk for retirement due to health reasons was even higher when participant experienced both tiredness and feeling worn out. Dissatisfaction with sleep did not predict retirement due to health or other reasons.
Conclusions: Our results highlight that workers at risk of subsequent retirement due to health reasons may be identified with rather simple questions on tiredness and feeling worn out even among generally healthy older workers.